PERSELISIHAN MASYARAKAT IV KOTO DENGAN V KOTO DI KOTA PADANG PANJANG TAHUN 1815 - Febby Indri R; Ridwan Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Disputes are a form of discord by individuals or groups because they have different attitudes, beliefs, values or needs. The process that occurs when an individual or group negatively affects another individual or group by engaging in physical violence that makes the other person's feelings and feelings disrupted. The purpose of this research is to know the cause of the dispute of society IV Koto with V Koto, to know the characters involved in the dispute between society IV Koto with V Koto, to know the resolution happened in dispute between society IV Koto with V Koto, To explain the impact of the dispute between the community of Koto IV and V Koto. The method used in this research is qualitative. Data obtained from the interviews are then analyzed in their own language. The location of the research is Padang Panjang City. This research began to be implemented after the exam proposal until this thesis is completed. Data collection techniques used are documentation techniques, interview techniques and literature study techniques. The result of the research indicates that there has been a dispute between IV Koto and V Koto in Padang Panjang City in 1815 because the problem of gambling and dispute took victim from community IV Koto.Keyword: Community IV Koto with V Koto, Dispute